Seismology at School in Nepal: A Program for Educational and Citizen Seismology Through a Low-Cost Seismic Network - Subedi, Shiba; Hetényi, György; Denton, Paul; Sauron, Anne (Frontiers in Earth Science, 2020)
Nepal, located above the convergent India-Eurasia plate boundary, has repeatedly experienced devastating earthquakes. During the 2015 magnitude 7.8 Gorkha earthquake, an often-reported experience was that people were not aware of the threatening seismic hazard and have insufficient level of preparedness. An important source of the problem is that earthquake-related topics are not part of the school curriculum. Earthquake education reaching a broad group of the population early in their lives is therefore strongly needed. We established an initiative in Nepal to introduce seismology in schools, with focus on education and citizen seismology. We have prepared educational materials adapted to the Nepali school system, which we distributed and also share on our program’s website: http://seismoschoolnp.org. In selected schools, we also installed a low-cost seismometer to record seismicity and to allow learning-by-doing classroom activities. Our approach was very well received and we hope it will help making earthquake-safe communities across Nepal. The seismic sensor installed in schools is a Raspberry Shake 1D (RS1D), selected based on performance in laboratory tests and adequacy to field conditions. At a test site in Switzerland we were able to record magnitude 1.0 events up to 50 km distance with a RS1D. In Nepal, 22 such seismometers installed in schools create the Nepal School Seismology Network providing online data openly. The seismometer in each school allows students to be informed of earthquakes, visualize the respective waveforms, and estimate distance and magnitude of the event. For significant local and regional events, we provide record sections and network instrumental intensity maps on our program’s website. In 6 months of network operation, more than 194 local and teleseismic earthquakes of M≥4 have been recorded. From a local and a global catalogue, complemented with our own visual identifications, we provide an earthquake wave detectability graph in distance—magnitude space. Based on our observations, we calibrate a new magnitude equation for Nepal, related to the epicentral distance D[km] and to the observed peak ground velocity PGVv[µm/s]. The calibration is done to best fit local catalogue magnitudes, and yields the following result: M = 1.05log10(PGVv) + 1.08log10(D) + 0.75